If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 5 + -4(x + 1) = 9x + 7 Reorder the terms: 6x + 5 + -4(1 + x) = 9x + 7 6x + 5 + (1 * -4 + x * -4) = 9x + 7 6x + 5 + (-4 + -4x) = 9x + 7 Reorder the terms: 5 + -4 + 6x + -4x = 9x + 7 Combine like terms: 5 + -4 = 1 1 + 6x + -4x = 9x + 7 Combine like terms: 6x + -4x = 2x 1 + 2x = 9x + 7 Reorder the terms: 1 + 2x = 7 + 9x Solving 1 + 2x = 7 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 1 + 2x + -9x = 7 + 9x + -9x Combine like terms: 2x + -9x = -7x 1 + -7x = 7 + 9x + -9x Combine like terms: 9x + -9x = 0 1 + -7x = 7 + 0 1 + -7x = 7 Add '-1' to each side of the equation. 1 + -1 + -7x = 7 + -1 Combine like terms: 1 + -1 = 0 0 + -7x = 7 + -1 -7x = 7 + -1 Combine like terms: 7 + -1 = 6 -7x = 6 Divide each side by '-7'. x = -0.8571428571 Simplifying x = -0.8571428571
| 7a+5=54 | | 6x+8=-7x+8(-2x+1) | | 11-.1x=10 | | 7+79+x=347 | | 4x^2-.25=0 | | 6x(x-1)=35-7x | | y+30=3y-50 | | 2/3(6x-9)=x+5 | | 5(-3)(5)-2(2)=0 | | -8+-6x+9x^2=0 | | 5(-3)(5)-2(2)= | | 1415-16x^2=0 | | -92=m-2(10-4m) | | 0.44-0.05x=0.25x-0.1 | | .5(x+7)-3=7 | | 4.5x+3.4=2x+8.4 | | -8(-4a-6)+3=-205 | | 4h^2+18h-26=0 | | 2(-3)+3(2)= | | 15=-15-8x | | 130-(7x+14)=7(x+8)+x | | x^2-36x=205 | | 2-8(r-5)=90 | | 3+2z-2=8z+3-5z | | 4x-3x+x+2= | | 42x=-3x^2-147 | | 6(1-7b)=-246 | | 4(3x+4)=88 | | x^2+9x+2= | | 7x+8=-83 | | 5(3n-5)+2n=-93 | | 4+3x-2=8x+3-4x |